Goniolimon africanum (Plumbaginaceae), a new endemic species from North Africa - Buzurović, Uroš; Bogdanović, Sandro; Brullo, Salvatore; Niketić, Marjan; Tomović, Gordana (Phytotaxa, 2018)
A new species, Goniolimon africanum is described and illustrated from Algeria and Tunisia (North Africa). This study, based on investigations of herbarium specimens and data from literature, highlights the fact that this species was collected for the first time by Ernest Cosson and provisionally named ‘Goniolimon luteolus’ nom. nud., while it was later attributed to G. tataricum. A detailed morphological study, carried out on some related European species of Goniolimon, has emphasized that African populations are taxonomically well differentiated from European ones. Its distribution, ecology and relationships are also examined. A table comparing the new species with the closest allied European species of Goniolimon is provided.